Can Renewable Energy Sustain an Age of Cheap Energy? - Ishida, Hazuki (Journal of Technology Innovations in Renewable Energy, 2013)
Utilizing renewable energy depends more or less upon non-renewable energy sources (mainly fossil fuels), and which implies that a continuous rise in energy prices is inevitable without technological progress in saving fossil fuel use. Using a simple Hotelling model of optimal resource extraction, this paper explores the conditions under which the continuous price rise of renewable energy is restrained in the presence of technological progress in harnessing renewable energy. The results show that to sustain the age of cheap energy, the growth rate of technology in harnessing renewable energy has to be larger than the discount rate. Even if the rate of the technological progress is faster than the discount rate, the energy price may continue to rise until the conventional system of energy generation from fossil fuels is obsolete.